Aktualisasi Prinsip Pemberdayaan Islam Tenaga Pendamping Profesional Indonesia (TPPI) Pada Program Pembangunan Dan Pemberdayaan Masyarakat DesA (P3MD) - Suprawan, Lalu; Sabirin (Al-Madani: Jurnal Pengabdian Pada MAsyarakat, 2022)
A man behind the gun, it seems that this quote deserves to be attached to the village assistant (TPPI) where with their different efforts in mentoring they are able to assist the village towards religious empowerment through the principles of empowerment contained in the Al-Quran and Hadith. In this paper it will be shown what and how the village assistants behave in applying the empowerment principle in terms of ukhuwah, ta'awun, and equality.